Implementing English Kids’ Song Media to Improve Students’ Vocabulary Achievement - Ni Made Asri Suwandesi; Ni Made Ratminingsih; Kadek Sintya Dewi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
A song becomes a great English learning media in enhance students English skill, especially vocabulary achievement. This study was conducted to improve students’ vocabulary achievement through English kids’ song media in the first academic year. The subjects of this study consisted of 33 fifth-grade students. This study employed Classroom Action Research (CAR). The research design used in this study was a collaborative classroom action research, which means that the researcher collaborated with the real fifth-grade teacher as a collaborator and an observer. This study consisted of two cycles. Each cycle is consisted of two meetings that contained four phases; planning, acting, observing, and reflecting. The data for this study were acquired through observation, post-tests, and interviews. The result of the observations showed that all aspects of the observation checklist were fulfilled and completed well by the researcher in each meeting in the first and second cycles. The improvement could be seen in the increase of students’ mean scores from 64 in the preliminary study, 72 in the first cycle, to 79 in the second cycle. The result of the interview showed that all students gave positive responses to the implementation of English kids’ song media to improve students’ vocabulary achievement in teaching and learning process. Moreover, English kids’ song can be an alternative media in teaching and learning vocabulary.